Electric Conductivity and Power of Hydrogen Value of Processed Seawater Using a Distillation Tool - Muliyadi Muliyadi; Idayani Sangadjisowohy (Jurnal Ilmu dan Teknologi Kesehatan, 2021)
Water pollution in the coastal areas of Ternate has shown a serious increase. It can be seen from the amount of garbage and the appearance of water turbidity in areas near residential areas. Based on a preliminary study, several residents behind the mountain also complained about the brackishness of their wells due to seawater intrusion. This study aims to determine the effectiveness of the distillation method on decreasing the value of electrical conductivity and power of hydrogen (pH) in seawater. This research is an experimental study with a post-test only group control design with a sample of 10 litres of liquid waste from three places, namely Muara Maliaro, Muara Pasar Sayur, Muara Pelabuhan Besar. The results of this study were processed using data processing software with paired T-test and Wilcoxon. The average value of DHL in samples 1, 2, 3 after distillation was carried out successively was 116 mhos/cm, 109.33 mhos/cm, 109.66 mhos/cm. The average pH value in samples 1, 2, 3 after distillation in all samples have shown normal values ​​with an average of 7. There is a difference in the DHL value before and after distillation with the Sig value (2-tailed), which is <0.05. There is a different pH value before and after distillation with the Sig value (2-tailed) <0.05. Distillation equipment can reduce the value of electrical conductivity and pH in seawater.